TINGKAT KEPUASAN WISATAWAN TERHADAP KUALITAS PELAYANAN TOKYO TOWER MELALUI METODE IMPORTANCE PERFORMANCE ANALYSIS - Rizka Amanda Putri Matrutty; Meizar Rusli (Jurnal Pariwisata Tawangmangu, 2026)
Service quality is an important factor in determining tourist satisfaction at tourist destinations. This study aims to determine the level of tourist satisfaction with the service quality of Tokyo Tower, based on the SERVQUAL dimensions, using the Importance-Performance Analysis (IPA) method. The SERVQUAL dimensions used include tangible, reliability, responsiveness, assurance, and empathy. This study employed a descriptive quantitative approach, with data collected through questionnaires distributed to 60 tourists who had visited Tokyo Tower. The sampling technique used was accidental sampling. Data were analyzed using validity and reliability tests, and IPA to map service attributes into four improvement-priority quadrants. The results are expected to identify service attributes that should be prioritized for improvement, maintained, or reduced based on tourists' perceptions of importance and performance. The findings can serve as an evaluation tool for Tokyo Tower management to improve service quality and enhance tourist satisfaction.